High resolution synchrotron imaging of wheat root hairs growing in soil and image based modelling of phosphate uptake. Issue 4 (22nd April 2013) - Keyes, Samuel D.; Daly, Keith R.; Gostling, Neil J.; Jones, Davey L.; Talboys, Peter; Pinzer, Bernd R.; Boardman, Richard; Sinclair, Ian; Marchant, Alan; Roose, Tiina
Summary: Root hairs are known to be highly important for uptake of sparingly soluble nutrients, particularly in nutrient deficient soils. Development of increasingly sophisticated mathematical models has allowed uptake characteristics to be quantified. However, modelling has been constrained by a lack of methods for imaging live root hairs growing in real soils. We developed a plant growth protocol and used Synchrotron Radiation X‐ray Tomographic Microscopy (SRXTM) to uncover the three‐dimensional (3D) interactions of root hairs in real soil. We developed a model of phosphate uptake by root hairs based directly on the geometry of hairs and associated soil pores as revealed by imaging. Previous modelling studies found that root hairs dominate phosphate uptake. By contrast, our study suggests that hairs and roots contribute equally. We show that uptake by hairs is more localized than by roots and strongly dependent on root hair and aggregate orientation. The ability to image hair–soil interactions enables a step change in modelling approaches, allowing a more realistic treatment of processes at the scale of individual root hairs in soil pores.